A comunicação organizacional no processo de articulação das instituições de ensino superior públicas maranhenses em favor da internacionalização. - CASTRO, Paloma França (2021)
As an ancestral practice, internationalization is now one of the main forces that are impacting and developing higher education in the world as it has changed to face the challenges ordered by society. Changing can be defined as a key feature of the internationalization of higher education as a process of continuous transformation. In the face of a fast-paced process of internationalization, higher education institutions, one of the main actors involved in the internationalization of education, are not always able to articulate themselves properly to manage this process, which affects their academic development and social role. Therefore, institutional internationalization has become an essential issue in higher education institutions. In this way, considering that the institutional articulation necessary for the establishment of the internationalization process in higher education institutions is permeated by the communication practices developed by higher education institutions, organizational communication assumes a leading role in this scenario. In doing so, this study proposes to analyze how organizational communication can contribute to the process of internationalization of public higher education institutions headquartered in Maranhão, taking as a reference the study developed by the Advisory Network for International Affairs of Education and Research Institutions of the State of Maranhão - ReINTER, created by the State Secretariat for Science, Technology and Innovation - SECTI in 2016. In this study, we made use of bibliographical research, whose literature review allowed us to show concepts and demonstrate the context in which the internationalization of teaching and organizational communication have been observed in this study; documentary research, through which it was possible to collect internationalization data in the institutions that make up ReINTER; and the application of a questionnaire, which made it possible to uncover weaknesses and, so, point out possible communication strategies that can help in solution or, at least, reduce these vulnerabilities. Finally, it was identified that the network still sees communication as an instrumental way, not as a strategic area for achieving ReINTER's goals.